Comparison between 400&800 microgram rectal misoprostol to prevent PPH when used before cesarean section immediately - بدور, منال; أحمد حسن يوسف ,; ثورة نعيسة, (Latakia University Journal -Medical Sciences Series, 2022)
Background: Postpartum hemorrhage (PPH) remains a common cause of maternal mortality worldwide. Medical intervention plays an important role in the prevention and treatment of PPH. Misoprostol, a prostaglandin E1 analogue with strong uterotonic properties, has been suggested as an alternative to injectable uterotonic agents for preventing PPH following vaginal or cesarean deliveries. Aim: This study was designed to compare the effectiveness of administration of different doses of rectal misoprostol before cesarean section to reduce intra- and postoperative blood loss. Materials and Methods: A prospective, randomized, observational, descriptive clinical trial conducted at Obstetrics and Gynecology Department in Tishreen University Hospital, Lattakia, during the period from February 2020 to February 2021. The study included 160 term pregnant woman scheduled for elective cesarean section where participants received either 400- or 800-μg misoprostol rectally before cesarean section. Primary outcome measures were estimated amount of intraoperative and postoperative (2 hours) blood loss and changes in hemoglobin and hematocrit levels 3 hours after delivery. Results: Intraoperative and postoperative blood loss was significantly lower in patients who received 800-μg misoprostol (345 ± 147 ml) than those who received 400-μg (460 ± 150 ml). The differences between the preoperative and postoperative hematocrit and hemoglobin values were significantly lower in in patients who received 800-μg misoprostol than those who received 400-μg. The incidence of side effects as fever and chills was higher in patients who received 800-μg misoprostol. Admissions to the neonatal intensive care unit and Apgar scores at 1 and 5 minutes were comparable between the 2 groups. Conclusion: Rectal administration of 800-μg misoprostol for the prevention of post-partum hemorrhage and decreasing intraoperative blood loss during caesarian section is a good alternative to 400-μg.